State of Competition in the Insurance Industry: Selected Asian Countries - Melanie S. Milo (Philippine Institute for Development Studies (PIDS), 2003)
This paper is a preliminary review of the state of competition in the insurance industry of selected Asian countries. In particular, it explores how competition has been affected by the market structure and the regulatory regime in the insurance industries of the ASEAN5 economies Indonesia, Malaysia, Philippines, Singapore and Thailand. It has four main sections. Section II surveys the market structure and overall performance of the insurance industry in the ASEAN5 economies. The third section then looks at the regulatory framework, including the major financial sector reforms that have been undertaken and the factors driving these reforms. In particular, it shows how the regulatory framework in itself can be an important determinant of the structure and performance of the industry, particularly public policy towards entry and the critical role of the industry regulator. Finally, what competition policy implies for the industry is discussed in the fourth section.
Keywords: 330; insurance industry; insurance regulation; Versicherung; Versicherungsmarkt; Regulierung; Marktstruktur; Wettbewerb; Indonesien; Malaysia; Philippinen; Singapur; Thailand